MAPPING OF S-WAVE ATTENUATION FIELD USING THE CODA ENVELOPES OF LOCAL EARTHQUAKES AND QUARRY BLASTS FOR THE EAST KAZAKHSTAN REGION ON THE DATA FROM PERMANENT AND TEMPORARY SEISMIC STATIONS - Yu. F. Kopnichev; I. N. Sokolova (Геодинамика и тектонофизика, 2023)
The paper considers the heterogeneities of short-period shear waves attenuation field in the east Kazakhstan lithosphere including the region of the Semipalatinsk Test Site where a lot of test detonations of nuclear weapons were performed underground in the past. The common S-waves coda envelopes were obtained by the records of near calibration explosions and quarry blasts as well as local earthquakes on the data from permanent and temporary stations. The obtained data allowed us to create attenuation field sections in the lithosphere of the considered region. The attenuation field heterogeneities were mapped for the lower crust and uppermost mantle of the east Kazakhstan. Very low Q-factor values (Qs~40–55) correspond to several stations installed in the area of the Balapan test site where the most powerful test explosions were conducted. These values are much lower than the minimum values corresponding to a large number of stations installed in seismically active region of the Northern Tien Shan. It is supposed that this is due to upwelling of deep-seated fluids along the active fault zones under a long-term intensive vibration effect. The obtained data can be used to reveal the zones having high concentration of fluids in the lithosphere parts of probable large earthquake generation. This information is quite important due to the planned construction of nuclear power plant in the east Kazakhstan region.